Control of Auxiliary Materials in the Biodiesel Process Using the Min-Max Stock Method at PT. Permata Hijau Palm Oleo Belawan - Zebua , Agung Persada; Suliawati, Suliawati; Arfah, Mahrani (SEAN Institute, 2024)
Control of Auxiliary Materials in the Biodiesel Manufacturing Process Using the Min-Max Stock Method at PT. Permata Hijau Palm Oleo Belawan. The main reason why companies store raw materials in large quantities is as safety stock if there is a delay in delivery from suppliers so that the production process does not stop. This research was carried out on four auxiliary materials used for the Biodiesel manufacturing process, namely, Methanol, Catalist, HCl, and NaOH at PT. Permata Hijau Palm Oleo Belawan. From the research results, it was found that the final inventory of auxiliary materials during 2022 and 2023 was very large compared to inventory calculations using the Min-Max Stock method, namely for Methanol auxiliary materials, namely 390,182 Kg (2022) and 2,095,097 Kg (2023) compared to using the Min-Max Stock method of 316,852 Kg (2022) and 409,299 Kg (2023), with an investment cost of Rp. 10,898,701,800 Catalist, namely 1,130,654 (2022) and 1,776,481 Kg (2023) using the Min-Max Stock method of 76,325 Kg (2022) and 92,518 (2023), with an investment cost of Rp. 20,713,186,300, NaOH, namely 173,197 Kg (2022) and 152,905 Kg (2023) with the Min-Max Stock method of 36,466 Kg (2022) and 35,106 Kg (2023) with an investment cost of Rp. 2,107,404,600, HCl namely 130,767 Kg (2022) and 146,161 Kg (2023) using the Min-Max Stock method of 69,337 Kg (2022) and 63,821 Kg (2023) with an investment cost of Rp. 230,552,000. From the research results it can be concluded that controlling the inventory of auxiliary materials at PT. PHPO Belawan is still not optimal. The final inventory of auxiliary materials is still very large and the largest is Methanol auxiliary materials in 2023, Catalist in 2022 and 2023.